Mass fractal characteristics of sonogels prepared from sonohydrolysis of tetraethoxysilane with additions of dimethylformamide - Vollet, D. R.; de Sousa, W. A. T.; Donatti, D. A.; Ruiz, A. Ibanez (Elsevier B.V., 2007)
Wet silica gels with similar to 1.4 x 10(-3) mol SiO2/cm(3) and similar to 90 vol.% liquid phase were prepared from the sonohydrolysis of tetraethoxysilane (TEOS) with different additions of dimethylformamide (DMF). Aerogels were obtained by CO2 supercritical extraction. The samples were studied mainly by small-angle X-ray scattering (SAXS) and nitrogen adsorption. Wet gels exhibit a mass fractal structure with fractal dimension D increasing from 2.23 to 2.35 and characteristic length xi decreasing from similar to 9.4 nm to similar to 5.1 nm, as the DMF/TEOS molar ratio is increased from 0 to 4. The supercritical process apparently eliminates some porosity, shortening the fractality domain in the mesopore region and developing an apparent surface/mass fractal (with correlated mass fractal dimension D-m similar to 2.6 and surface fractal dimension D-s similar to 2.3) in the micropore region. The fundamental role of the DMF addition on the structure of the aerogels is to diminish the porosity and the pore mean size, without, however, modify substantially the specific surface area and the average size of the silica particle of the solid network. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: synchrotron radiation; porosity; nanoparticles; silica; sol-gel; aerogel and solution chemistry; adsorption